Hominin fire use in the Okote member at Koobi Fora, Kenya: New evidence for the old debate. Issue 133 (August 2019) - Hlubik, Sarah; Cutts, Russell; Braun, David R.; Berna, Francesco; Feibel, Craig S.; Harris, John W.K.
Abstract: Hominin fire use in the early Pleistocene has been debated since the early 1970s when consolidated reddened sediment patches were identified at FxJj20 East and Main, Koobi Fora, Kenya. Since then, researchers have argued for evidence of early Pleistocene fire use at a handful of archaeological sites with evidence of combustion. Some argue that morphological evidence of early Homo erectus fossils indicates a dietary shift to higher quality food sources, which could be achieved by cooking. Others contend that fire use does not become a regular behavior until later, in the middle Pleistocene, when archaeological sites begin to show regular evidence for fire use. An early date for hominin control of fire would help to explain the grade changes seen with the appearance of H. erectus, while a later date would mean that fire would have had little influence on the early development of the lineage. Early hominins would have encountered fire regularly on the landscape, increasing the possibility of hominins interacting with and habituating to natural landscape fire. Only a detailed understanding of the patterns of controlled and natural fires can lead to understanding of early hominin fire use. We present new work on the evidence of fire at the FxJj20 Site complex in Koobi Fora, dated to 1.5 Ma. We highlight evidence of burning found on site through Fourier Transform Infrared spectrometry, and describe ongoing work to investigate the association of hominin behavior and fire evidence. We present data supporting the hypothesis that the site is undisturbed and discuss spatial relationships showing burned material associated with non-burned material. We present data on a type of stone fragment, the Thermal Curve Fragment (TCF), which is indicative of knapped material being exposed to high heat. Finally, we suggest future directions on the topic of fire in the early Pleistocene.